Snoopy$1 (Bs tennis book :s featuring Snoopy at Wimbledon and Snoopy$1 (Bs tournament tips s - Schulz, Charles M. (Charles Monroe), 1922-2000. (New York : Holt, Rinehart, and Winston, 1979)
Follows the tennis exploits of Snoopy as he is victimized by bad line calls, realizes his dream of going to Wimbledon, and withstands the agony of insensitive or inanimate doubles partners.
Consists mainly of selections from the author$1 (Bs comic strip Peanuts.s
Keywords: Tennis -- Caricatures and cartoons; Tennis -- Cartoons and comics; Cartoons and comics